Route computation in large road networks: A hierarchical approach - Jagadeesh, G. R. (2014)
The optimal route between a given origin and destination needs to be computed in a fast and efficient manner in dynamic route guidance systems. Conventional routing algorithms have been found to be inadequate when applied directly to large road networks. Algorithms based on the concept of hierarchical abstraction make use of the knowledge about the road network to reduce search and provide near-optimal solutions. A generic procedure is presented for organising a given road network as a multiple-layer hierarchy. An efficient hierarchical routing algorithm is proposed, which breaks down the route search into a number of individual searches in small sub-networks. The algorithm incorporates a heuristic layer-switching technique to improve its performance without compromising the accuracy. The hierarchical routing algorithm was tested on the road network of Singapore and the solutions were found to be comparable to the optimal least-cost paths.